ANALYSIS OF FACTORS INFLUENCING INVESTMENT DECISION - Hesniati Hesniati (Journal of Global Business and Management Review, 2020)
Gold presents as important role in an investor's portfolio because it provides stability of returns and favorable opportunity to improve investor wealth. Investment decision making depend on intrinsic factor investor behavior. Therefore, this study aims to investigate the impact of behavioral finance toward investment decision in gold instrument. Anchoring, availability bias, information asymmetry, representative bias, and risk aversion are chosen as behavioral finance factors. This study is conducted in Batam City Indonesia with 143 respondents and analysed using multiple linear regression analysis. Findings reveal behavioral factors such as information asymmetry and availability bias have significant impact on investment decision. However, the other independent variables do not have significant impact on investment decision.